Polymorphic Spin, Charge, and Lattice Waves in Vanadium Ditelluride. Issue 11 (6th February 2020) - Won, Dongyeun; Kiem, Do Hoon; Cho, Hwanbeom; Kim, Dohyun; Kim, Younghak; Jeong, Min Yong; Seo, Changwon; Kim, Jeongyong; Park, Je‐Geun; Han, Myung Joon; Yang, Heejun; Cho, Suyeon
Abstract: Lattice distortion, spin interaction, and dimensional crossover in transition metal dichalcogenides (TMDs) have led to intriguing quantum phases such as charge density waves (CDWs) and 2D magnetism. However, the combined effect of many factors in TMDs, such as spin–orbit, electron–phonon, and electron–electron interactions, stabilizes a single quantum phase at a given temperature and pressure, which restricts original device operations with various quantum phases. Here, nontrivial polymorphic quantum states, CDW phases, are reported in vanadium ditelluride (VTe2 ) at room temperature, which is unique among various CDW systems; the doping concentration determines the formation of either of the two CDW phases in VTe2 at ambient conditions. The two CDW polymorphs show different antiferromagnetic spin orderings in which the vanadium atoms create two different stripe‐patterned spin waves. First‐principles calculations demonstrate that the magnetic ordering is critically coupled with the corresponding CDW in VTe2, which suggests a rich phase diagram with polymorphic spin, charge, and lattice waves all coexisting in a solid for new conceptual quantum state‐switching device applications. Abstract : Polymorphic type 1 and 2 charge density wave (CDW) states are reported at ambient conditions in vanadium ditelluride (VTe2 ). The CDW phases, involving polymorphic spin waves, are distinct from the conventional formation of CDWs with electron–phonon interactions. The interwoven nature of the three degrees of freedom (spin, charge, and lattice) in VTe2 allows new conceptual quantum state‐switching device applications.